The Boundless Present Space and Time in the Literary Fairy Tales of Novalis and Tieck - Birrell, Gordon (UNC Studies in the Germanic Languages and Literatures, 1979)
This volume is a study in the Romantic reshaping of space and time to evoke the fantastic interior landscape and the temporal dynamics of subjective experience. Close textual analysis is coupled with frequent reference to literary and intellectual history in the reassessment of the narrative art of Novalis and Tieck. The author examines Novalis' "Hyazinth und Rosenblüte", "Atlantis", "Arion" and "Eros und Fabel" as well as Tieck's "Der blonde Eckbert" and "Der Runenberg". A concluding chapter examines spatio-temporal patterns in the Romantic fairy tale at large.